International Experience of Legal Regulation of Liability for Insult of Police Officers and Possibilities of Its Use in Ukraine (Law and Safety, 2021)
The article highlights the problem of the need to strengthen the legal protection of employees of the National Police of Ukraine, who are subjected to illegal encroachments on their honor and dignity while performing their official duties.It is proved that there are acts concerning insults of police officers and insults or slanders committed against ordinary people in the normative legal acts of the countries of Europe and the former CIS. As a rule, insulting or slandering a law enforcement officer is a crime, while other actions are administrative offenses. Such actions have a qualified composition, which is manifested in the public dissemination of such insults or slander. It is argued that punishment for insulting a police officer is applied only in cases related to the performance of their official duties. Otherwise, the case will be considered in the usual way; the corpus delicti of such a crime may be recognized as qualified if such slander or insult is disseminated through the media or through the Internet.The current state of legal regulation of legal liability for insult and defamation of police officers in the Republic of Belarus, Kazakhstan, Poland, Germany, France and Spain is analyzed. Based on the study, the propositions to the Law of Ukraine «On the National Police» are formulated that are aimed at regulating the professional guarantees of police activities. It is emphasized that interfering in the activities of a police officer, failure to comply with his legal requirements, obstruction of the exercise of his respective powers, insult or slander against a police officer related to his official activities, insult to the police, as well as any other illegal actions they must be held legally liable for the police officer. The position that the profile law should enshrine in law the state protection of life, health, honor, dignity of a police officer, his professional reputation, members of his family, as well as property belonging to him and his family members from illegal encroachments in connection with the performance of official duties.
Keywords: National Police; a police officer; insult; slander; an administrative offense; legal protection